Strings : an introduction to musical instruments - Lillegard, Dee. (Chicago : Childrens Press, 1988)
A brief introduction to the musical instruments of the strings family.
13
Keywords: Stringed instruments -- Juvenile literature; Musical instruments; Stringed instruments